Implementasi Konseling Individual Dalam Meningkatkan Hubungan Sosial Teman Sebaya - Fadzilah, Sarah; Hermatasiyah, Nur; Alkafi, Aceng Akhmad Munanzdar (Al-Ittizaan: Jurnal Bimbingan Konseling Islam, 2025)
This research is the result of three individual counseling meetings on 3 students of class VIII SMP IT Al-Luthfah, the main basis of the counseling conducted is preventive, curative, and development. This research is also based on the results of the assessment with the BK instrument, namely the Inventory of Developmental Tasks (ITP) which produces the lowest items related to relationships with peers, then from these results an activity design is formed, such as (1) Introductions, approaches, and establishing an agreement on the time and place of counseling, (2) Collecting client data or information by assessment, (3) Setting activity strategies, (4) Implementation of counseling, (5) Evaluation and results. This research uses a descriptive research methodology with a qualitative approach, which focuses on (1) The results of the management of thequestionnaires, (2) results of the lowest developmental level one-point aspects, (3) and descriptions of direct observation results and reflection/evaluation sheets to determine the level of understanding reflection/evaluation sheets and interviews to determine the level of problems experienced by students. The results of the counseling meeting show that the level of student problems is quite crucial to improve and by providing individual counseling services the student concerned feels this meeting is appropriate for his development to be more optimal.